IRF6 Genetic Variation and Maternal Smoking During Pregnancy in Cleft Lip/Palate - Vieira, Alexandre R.; Koruyucu, Mine; Bekele, Eyosiyas K.; Seymen, Figen; Modesto, Adriana (Frontiers in Dental Medicine, 2021)
The goal of the present work was to revisit published data to test if genetic variation in interferon regulatory factor 6 (IRF6) is associated with children born with cleft lip with or without cleft palate (CL/P) for cases with positive history of maternal smoking. From the 573 individuals originally studied, this reanalysis focused on 57 who had a positive history of maternal smoking during pregnancy (39 born with CL/P and 18 born without CL/P). Seven IRF6 markers (rs4844880, rs2235371, rs2013162, ra861019, rs2073487, rs642961, and rs658860) were tested for over-transmission of alleles and an alpha of 0.05 was considered statistically significant. All individuals born with CL/P were homozygous for the wild type allele of rs2235371 in comparison to just two individuals born without clefts (p = 0.0000001). For rs861019, individuals born with CL/P were more likely to have the variant allele (p = 0.006). A similar trend was seen for rs642961 (p = 0.09). The results suggest that statistical evidence of over-representation of IRF6 alleles in individuals born with CL/P may be unveiled only when maternal smoking during pregnancy is used as the inclusion criterion in the analysis.